A Plastic Design Method for RC Moment Frame Buildings against Progressive Collapse - Faghihmaleki, Hadi (UI Scholars Hub, 2017)
In this study, progressive collapse potential of generic 3-, 8- and 12-storey RC moment frame buildings designed based on IBC-2006 code was investigated by performing non-linear static and dynamic analyses. It was observed that the model structures had high potential for progressive collapse when the second floor column was suddenly removed. Then, the size of beams required to satisfy the failure criteria for progressive collapse was obtained by using the virtual work method; i.e., using the equilibrium of the external work done by gravity load due to loss of a column and the internal work done by plastic rotation of beams. According to the nonlinear dynamic analysis results, the model structures designed only for normal load turned out to have strong potential for progressive collapse whereas the structures designed by plastic design concept for progressive collapse satisfied the failure criterion recommended by the GSA code.